Integrating one health in national health policies of developing countries: India's lost opportunities. Issue 1 (December 2016) - Chatterjee, Pranab; Kakkar, Manish; Chaturvedi, Sanjay
Abstract Background Globally, the threat of infectious diseases, particularly emerging infectious diseases, originating at the human-animal-environment interface, has caught health systems off guard. With forecasts that future pathogen emergence will be centred in hotspots in Asia, Africa, and Latin America, the need to prepare policy frameworks that can combat this threat is urgent. Discussion Emergence of diseases such as avian influenza and Ebola virus disease, which threatened social disruption, have established the need for intersectoral coordination/collaboration. These events led to the initiation of establishing institutionalised collaborative frameworks in India to adopt a One Health approach to disease prevention and control. However, the gains made in influenza control could not be adapted to other infectious diseases. Intersectoral coordination was briefly carried out, more as a reactive response to threats. The systemic failure to sustain such efforts have therefore, only undermined a coordinated response. The recent draft National Health Policy, 2015, has also failed to establish the need for intersectoral coordination in disease control approaches. Neglecting the need to endorse linkages between human health, animal health and husbandry, agriculture, and environmental sectors, has led to duplicative and weak response systems. The absence of health impact assessment with respect to the development agenda in policies, has cast negative effects on the health and wellbeing of man, animal, and the environment. Lack of attention to building core capacity in these critical sectors has further raised challenges in designing and deploying mitigation strategies. With developing countries like India being home to a major portion of the world's poorest livestock farmers, the absence of a policy discourse that endorses the One Health approach in development and health policies is a major hurdle in eliminating poverty and poverty-related diseases. Conclusions The adoption of One Health approaches in health and related sectoral policies is a critical policy requirement for India and other developing countries. The goal should be to not just establish preparedness plans, but also to encourage a policy environment where assessment and mitigation of downstream impacts of different agenda are incorporated.